MEMBEBASKAN RUANG KELAS PAI DARI KEKERASAN SIMBOLIK MELALUI PENDEKATAN HUMANISTIK - Nadia Amanda (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
Symbolic violence in Islamic Religious Education (PAI) classrooms is a subtle yet systemic form of domination, manifested through judgmental language, asymmetrical power relations between teachers and students, and the imposition of obedience without critical space. This situation weakens students’ religious reasoning and diminishes reflective spiritual awareness. This article emphasizes the urgency of adopting a humanistic approach in Islamic education, which upholds compassion, dialogue, and respect for individual potential as pedagogical foundations. The study aims to identify the forms of symbolic violence in PAI learning and explain how a humanistic approach can liberate classrooms from such domination. Using a qualitative-descriptive method, data were collected through classroom observations and interviews with teachers and students at a public junior high school in Banda Aceh, followed by thematic analysis. The findings reveal that symbolic violence persists in PAI teaching practices, yet a more humanistic strategy encourages dialogue, empathy, and critical awareness among students. The theoretical contribution of this paper lies in broadening the discourse of Islamic pedagogy toward symbolic liberation, while its practical significance offers recommendations for curriculum reform and teacher training based on humanistic ethics.